PERILAKU BIDAN KIA/KB DALAM PELAKSANAAN PROGRAM PREVENTION OF MOTHER TO CHILD TRANSMISSION (PMTCT) DI RUMAH SAKIT HAJI KOTA MEDAN TAHUN 2013 - Syarifah Harahap; Tukiman MKM; Vonny Syarah (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
The spread of HIV/AIDS in Indonesia is very fast . Currently there is no province in Indonesia that is free of HIV. PMTCT is an effort to prevent HIV transmission from mother to baby and an effective strategy to cover a broad spectrum, not only the housewives, but also to prostitute, female using injecting drug, migrant workers and others. In Medan there are two hospitals that serve governments PMTCT program. On observations found only 1 midwife who trained in PMTCT programs . The purpose of this study is to describe the behavior of midwives in the implementation of the PMTCT program (Prevention of Mother to Child Transmission) at Haji Hospital in Medan at 2013. This is a descriptive study with a qualitative approach using in-depth interviews to determine the behavior of midwives in the implementation of PMTCT (Prevention of Mother to Child Transmission) at Haji Hospital in Medan at 2013. Results showed midwives knowledge are still low about PMTCT (Prevention of Mother To Child Transmission) program. Midwives attitude positive outlook where midwives do not discriminate patients. Action of midwives in the face of patients didn’t match with the guidebook of PMTCT program. For thatis expected to the hospital to evaluatiate, train, and sosialize the PMTCT program, which is management of HIV infection and antiretroviral therapy for children, adolescent and adults, to assisting patient of PMTCT, and support to patient of PMTCT. Midwives is also espected to read and seek for more information about PMTCT.